2019
DOI: 10.1055/s-0039-1685448
|View full text |Cite
|
Sign up to set email alerts
|

Early Premature Infant Oral Motor Intervention Improved Oral Feeding and Prognosis by Promoting Neurodevelopment

Abstract: Objective This study aimed to explore the clinical significance of early premature infant oral motor intervention (PIOMI) in the prognosis of premature infants. Study Design Infants were randomly divided into an intervention group (n = 78) and a control group (n = 73). PIOMI was given to the intervention group 15 to 30 minutes before feeding once a day for 14 days. The whole procedure lasted 15 minutes, including oral stimulation and nonnutritive sucking. Oral feeding ability and neuromotor developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
5
23
1
2
Order By: Relevance
“…Gastrointestinal dysfunction and swallowing dysfunction prevent the early establishment of total oral nutrition, which may affect the postoperative recovery of patients. Studies have shown that early oral stimulation of infants with gastrointestinal dysfunction has a significant effect on the recovery of gastrointestinal function [4,5]. According to the literature review, no article has focused on the use of oral stimulation with breast milk in infants after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal dysfunction and swallowing dysfunction prevent the early establishment of total oral nutrition, which may affect the postoperative recovery of patients. Studies have shown that early oral stimulation of infants with gastrointestinal dysfunction has a significant effect on the recovery of gastrointestinal function [4,5]. According to the literature review, no article has focused on the use of oral stimulation with breast milk in infants after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In Xiao-Li Li et al's study (2020), PIOMI was given once per day for 14 days (33). In their study POFRAS score in the intervention group, increased by 6 points and in the control group by 3 points within 10 days.…”
Section: Discussionmentioning
confidence: 96%
“…oral function training can increase body growth and promote the development of gastrointestinal function and neuromotor function for premature birth, promote coordination of neuromotor function and increase the frequency of bowel movements, thereby improving the oral feeding ability of preterm infants and improving prognosis [9,22,23]. Regarding neurodevelopmental results at 18-26 months, those who have a corrected the gestational age at 40 weeks and reach full-mouth feeding have a better neurological prognosis, with reduced cognition, language, motor delays, less cerebral palsy and fewer adverse neurodevelopmental results [24].As the duration of oxygen inhalation increases,release of proinflammatory cytokines has been implicated in the development of systemic inflammation that contributes to BPD and ROP.In this study, we provided Intervention program to reduce the duration of oxygen use, reduced the incidence of BPD and ROP, and conductted early assessment to predict long-term outcomes and guide later rehabilitation treatment [25,26].…”
Section: Discussionmentioning
confidence: 99%